IMPLEMENTING CONTEXT CLUES STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION - Mutmainnah; St. Asriati AM; Ardiana (English Language Teaching Methodology, 2021)
This research aimed at finding out whether or not the implementation of context clues strategy is effective to improve students` reading comprehension at the eighth grade of MTs. Al-Falah Baras Mamuju Utara. The students` reading comprehension was restricted to two indicators namely literal comprehension (main idea and conclusion) and interpretative comprehension (conclusion). The researcher used preexperimental research. The researcher conducted pre-test, treatment and post-test in the total of six meetings. Reading test was used as instrument. The samples of the research were 23 students in VIII Putri class. The researcher took real data from school to know the students` reading comprehension. The result of the research showed that the t-test values in terms of literal comprehension (5.52) and interpretative comprehension (5.27). The final t-test values (5.395) were higher that ttable (1.717) at the level of significant (p) = 0.05 with degree of freedom (df) = 22. The differences between t-test and t-table was very significant. It means that the Null Hypothesis (H0) was rejected and Alternative Hypothesis (H1) was accepted. Therefore, it can be concluded that implementation context clues strategy is effective to improve students` reading comprehension